Export credit insurance-a comparison - Dieter Stentzel (Intereconomics, 1972)
Incessant growth of world trade and of overseas investments, and the shirts In their structure, are reflected In changes affecting International trade relations. The present article discusses the rising political and economic risks to which exports are exposed, and the consequent growth of demand for insuring export credits and direct Investments.
Keywords: 330; Foreign Trade